Poly(vinyl alcohol)/chitosan asymmetrical membranes: Highly controlled morphology toward the ideal wound dressing - Morgado, Patrícia Isabel da Cruz (2018)
Asymmetrical membranes have been reported as ideal wound dressings for skin regeneration. The usual methods (dry/wet-phase inversion) to produce those specific membranes are time consuming, and in majority of the cases demand the use of harmful organic solvents. In this study, supercritical carbon dioxide (scCO2)-assisted phase inversion method was applied to prepare poly(vinyl alcohol)/chitosan (PVA/CS) asymmetrical membranes. This technique can tailor the final structure of the dressing by tuning the processing conditions allowing the development of high porous materials with optimized morphology, mechanical properties and hydrophilicity. The PVA/CS dressings produced are recovered in a dry state but can form a hydrogel due to their high water uptake ability maintaining the moisturized environment needed for wound healing. The dressing presents a top thin layer of about 15 µm that allows gaseous exchange while barricading the penetration of microorganisms, and a sponge bottom layer that is able to remove excess exudates. A mathematical model based on Fick׳s second law of diffusion was developed to describe the pharmacokinetic release profile of a small drug (ibuprofen) from the swollen membrane in physiological conditions that mimic the wound. In vitro studies revealed that the dressings had excellent biocompatibility and biodegradation properties adequate for skin wound healing.